A Qualitative Study On The Impact Of Listening Podcast On Students’ Pronounciation - Bahri, Syamsul; Halimatussadiah, Halimatussadiah (Educator Development Journal, 2024)
This qualitative study investigate English Department Students’s perception of the impact of listening to podcast on their pronounciation ability.The s tudy was conducted with the participation of 7 students enrolled in English Education Department at Tarbiyah Faculty, Ar-Raniry State Islamic University. Data were collected through semi-structured interview, investigator notes and performance tracking record. The results show that podcast can help students in improving the quality of their pronunciation, effective to enhance pronunciation, helpful to develop students’ confidence in speaking English, and also encourage them to understand native better, to enrich students’ vocabularies, also useful to gain their listening and speaking skills. Regardless its positive aspects, there are some obstacles that the students faced when they listen to podcast, such as find unfamiliar vocabulary, sometimes podcast do not provide subtitles so that it makes more difficult for them to understand the contents of the podcast